Der Kalte Krieg und ich - Frank, Andre Gunder (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1998)
A personal trajectory is described, which took Frank as a child from Nazi Germany to dependency theory and global historical studies. This trajectory led him at various times to Castro's Cuba, Allende's Chile, and Breshnew's Russia Cold. On every station it was deeply influenced by the Cold War - as well in the West as in the East.